(untitled) (Journal of Graphic Engineering and Design, 2025)
With the development of modern technology, three-dimensional graphics (3D) are increasingly making their way into various fields such as design, advertising, packaging, industry and even medicine. Three-dimensional graphic elements can be not only modelled, but also apadted for the three-dimensional printing. However, the quality of the print is highly dependent on the printing method used, technological process and on the properties of the material. In this work, the models were created using 3D graphics software and tested after 3D printing. The new acrylic resin TGM-7, developed by AmeraLabs, was used for the 3D printing. During the testing process, the models were calibrated in order to obtain accurate and high-quality models with fewer inaccuracies or defects in the future and precise connections. During the experiments, a more significant change in dimensions was observed in the lower part of the models, which could have occurred due to the deposition of the polymer. Samples printed at a 45° angle had more accurate dimensions. The mechanism of parameters compensation in the XY and YX axis was demonstrated. During the work, the mechanical properties of the material were also determined, which are important for the many applications such as packaging, advertising items or other products subject to load. The acrylic resin, printed at different angles, exhibited plastic propertie, and samples printed at a 90° angle were better able to withstand dynamic loads, which averaged 206 N. The obtained results were applied to the creation and printing of an advertising model. Article history: Received (September 17, 2024); Revised (January 21, 2025); Accepted (January 29, 2025)